The Legal Status of the Presuggestion of Infinity In Notary Protection Efforts Related to the Making of Authentic Deeds - Syafii, Muhammad Amin; Handoko, Widhi (Jurnal Konstatering, 2022)
This study discusses the application of the legal position of the presumption of innocence in efforts to protect notaries regarding the making of authentic deeds in Pekalongan Regency. The position of a notary as a public official is related to making an authentic deed. The problems in this thesis are 1) constraints and solutions to the application of the presumption of innocence regarding the legal protection of a notary regarding the making of an Authentic deed by a notary 2) efforts to protect the notary regarding the deed he has made. The purpose of this study is to identify and analyze the obstacles and solutions to the application of the presumption of innocence regarding the legal protection of a notary regarding the making of an authentic deed by a notary. The method used in this research is a sociological juridical approach. The specification of this research uses descriptive analysis. The types and sources of data used in this study are primary data, namely from interviews, while secondary data is obtained through library research. The data collected in this study was divided into 2 (two), namely primary data collection which was carried out by interviews and secondary data collection which was carried out by collecting data contained in laws and regulations, articles, books and others. The data analysis method used in analyzing the data is qualitative analysis. Authentic deed essentially contains formal truth according to which the Notary is responsible for what is witnessed, namely what is seen, heard and also carried out by the Notary as a public official in carrying out his position. Notary legal protection is carried out by UUJN, Notary Association.Keywords: Authentic; Innocence; Presumption; Protection.